Talking the Talk: The Construction of Activist Capital in Argentinian Popular Social Movements - María Mercedes Palumbo (Íconos)
This article analyzes the socialization and construction of social and political capital in popular movements in the Metropolitan Area of Buenos Aires, Argentina. To analyze this case, we employ a theoretical framework which draws on the concepts of activist social capital and political socialization. These concepts serve to illuminate the native Argentinian concept of “talking the talk”, which is a key skill that contributes to the construction of one’s social capital as an activist. We argue that this know how is particularly important in determining one’s trajectory as an activist. However, understanding how to employ political discourse requires the adoption of a gender lens given that the mastery of “talking the talk” represents a greater challenge for female activists who have to overcome the impossibility of speaking. The reflections developed in this article problematize the everyday politics and practices of popular social movements given that the know-how of “talking the talk” contributes to the crystallization of the gendered social division of labor in social movements.